The Fleeting Effects of Disclosure Forthcomingness on Management's Reporting Credibility - Mercer, Molly (The Accounting Review, 2005)
This study provides a theoretical framework and experimental evidence on how managers' disclosure decisions affect their credibility with investors. I find that in the short-term, more forthcoming disclosure has a positive effect on management's reporting credibility, especially when management is forthcoming about negative news. However, these short-term credibility effects do not persist over time. In the long-term, managers who report positive earnings news are rated as having higher reporting credibility than managers who report negative earnings news, regardless of their previous disclosure decisions.